Effect of Slope on Stormwater Infiltration into Porous Asphalt Pavements - Yang, Qiuxia; Hu, Jiaxuan; Beecham, Simon (Sustainability, 2024)
Porous asphalt pavements and water-retentive asphalt pavements are widely used because of their ability to infiltrate both rainfall and stormwater runoff. There is very limited information available to assist designers of porous asphalt pavement systems to be installed on sloping sub-catchments. This is because the infiltration performance of these systems has only been investigated experimentally for horizontal pavements, and their performance on sloping terrains has only been investigated theoretically. This experimental study investigates the relationship between rainfall intensity, pavement slope, runoff and infiltration rates for dense-graded asphalt, porous asphalt and water-retentive asphalt concrete pavements. Three rates of simulated rainfall were applied to porous, water-retentive and dense-graded asphalt specimens set at three different pavement slopes, namely 0°, 3° and 5°. The relationship between the porosity and permeability of the porous asphalt pavements was also determined. A porosity of 20% resulted in a permeability of greater than 1 mm/s. It was found that the porous asphalt specimens had excellent runoff retention and infiltration rates at all slopes. The water-retentive asphalt specimens also produced good infiltration rates at horizontal slopes, but these decreased at higher pavement slopes.